Tinjauan Kelengkapan Penulisan dan Ketepatan Kode External Cause Kasus Kecelakaan Lalu Lintas di Siloam Hospital Kebon Jeruk - Lily Widjaja lily; Laela Indawati laela; Noor Yulia noor; Uli Shalatiya uli (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
In giving a code to a traffic accident case, it must be equipped with an external cause code, these external factors need attention because they are the cause of problems that need intervention in preventing, overcoming injuries, poisoning, or certain diseases. The purpose of this study is to identify the SOP for giving external cause codes for traffic accidents, calculate the completeness of external causes, measure the accuracy of the external cause code, find out the factors causing the inaccuracy of the external cause code. The research method is a quantitative descriptive method. The results showed that Siloam Hospital Kebon Jeruk did not yet have a special SOP for external causes for traffic accidents and from 64 samples of medical records it was known that the completeness of writing external causes was 57.81% and 42.19% were incomplete. The accuracy of the diagnostic code and the external cause is 64.96% and the incorrect is 35.04%. The factors causing the code inaccuracy are the lack of accuracy of the coder officer when giving the external cause code, the unclear writing of the doctor and the incomplete writing of the external cause, the absence of a special SPO for special coding for traffic accidents, and the SIMRS being inadequate to use the activity code which is a character code for traffic accidents. 5. The conclusion of this study is that the hospital does not have a special SOP for giving external cause codes to traffic accident patients, writing completeness is 57.81%, coding accuracy is 64.96%.